Bone Mineral Density In Hiv: A Comparison Of Hiv Positive Versus Negative Patient With Lower Limb Long Bone Fractures - Botha, Peter (Division of General Surgery, 2025)
Background: Osteoporosis is a global health issue causing a deterioration in bone microarchitecture, compromising bone strength. In South Africa (SA), the prevalence of osteoporosis is a growing concern for both HIV-positive and HIVnegative individuals. The aim of this study was to assess the impact of HIV infection on bone mineral density (BMD) in HIV-positive individuals and compare this to the BMD in HIV-negative individuals with traumatic long-bone fractures. In addition, we compared the impact of demographics, nutritional (albumin), Vitamin D status and smoking between HIV-positive and negative individuals. Patients and Methods: We retrospectively reviewed data from a prospectively collected database within the HIV in Orthopaedic Skeletal Trauma (HOST) study conducted at tertiary care hospitals. This study included all individuals with a confirmed HIV positive or negative status who had their BMD measurement performed using a calcaneal quantitative ultrasound scan (cQUS) and excluded those individuals who had never had a cQUS performed. Results: Of 400 individuals recruited from the parent study, 172 (43%) had their BMD measured. 27(15.7%) were HIV-positive. Overall, the BMD and T-scores were similar in both the HIV-positive and HIV-negative participants with a median BMD of 0.49 g/cm2 (0.23 – 0.71) within the HIV positive group; 0.49 (0.3-0.71) within the HIV negative group and an overall T-score of -0.8, with no statistical significance found between the two groups (p>0.050). Age, smoking status, Vitamin D, Albumin and BMI had no effect on BMD (p> 0.050). Conclusion: We found a higher proportion of patients with osteoporosis within the HIV-positive cohort, although not statistically significant and no statistically significant difference in the median BMD between the HIV -positive and HIVnegative subgroups. Neither age, smoking, vitamin D, albumin nor BMI was associated with a lower BMD